1990
DOI: 10.1037/0012-1649.26.4.649
|View full text |Cite
|
Sign up to set email alerts
|

Parental monitoring and perceptions of children's school performance and conduct in dual- and single-earner families.

Abstract: Relationships between parental monitoring and children's school performance and conduct were examined in 77 dual-and 75 single-earner families in which the eldest child was between 9 and 12 years old. During home interviews, mothers, fathers, and children reported on children's school grades, perceived academic competence, and perceived conduct. Parental monitoring (i.e., parents' knowledge about children's daily experiences) was assessed in 7 evening telephone interviews. Results indicated that less well-moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
179
2
5

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 237 publications
(201 citation statements)
references
References 22 publications
15
179
2
5
Order By: Relevance
“…For example, parent participation in family dinners and bedtime have been associated with greater social competence and positive social values in children (e.g., Fiese et al, 2002). Similarly, parent involvement and monitoring are associated with less delinquency in adolescence (e.g., Crouter, MacDermid, McHale, & PerryJenkins, 1990). It is no surprise then that many parents express concern that work responsibilities limit their ability to participate in family life and cultivate the affectional bonds that are consistent with their ideals.…”
Section: Family Children and Workmentioning
confidence: 99%
“…For example, parent participation in family dinners and bedtime have been associated with greater social competence and positive social values in children (e.g., Fiese et al, 2002). Similarly, parent involvement and monitoring are associated with less delinquency in adolescence (e.g., Crouter, MacDermid, McHale, & PerryJenkins, 1990). It is no surprise then that many parents express concern that work responsibilities limit their ability to participate in family life and cultivate the affectional bonds that are consistent with their ideals.…”
Section: Family Children and Workmentioning
confidence: 99%
“…For example, Crouter, MacDermid, McHale, and Perry-Jenkins (1990) found that lower levels of parental monitoring were associated with lowered rates of school competence among fourth-and fifth-grade boys. Additionally, Brown et al (1993) reported that levels of parental monitoring were positively correlated with adolescent grade point average (GPA).…”
Section: Parental Monitoring and Adolescent Adjustmentmentioning
confidence: 99%
“…The parent who maintains a dynamic balance between the dispositions of acceptance and guidance will remain open to the possibility that the unwanted workings of a child's mind and body may reveal themselves constitutive of something valuable, or at least as something meaningfully extraordinary about that particular child-to-be (Fox, 2008). Although dual-and single-earner boys and girls do not differ in the amount of monitoring they receive from their parents, dual-earner boys may be differentially susceptible to experiencing problems with school achievement or conduct in the face of poor parental monitoring (Crouter et al, 1990). Parental involvement in developing the individualistic plans is pertinent to the success of both their children's education and the plan its self (MacKichan & Harkins, 2013).…”
mentioning
confidence: 99%